Another gap on the rota: a scoping review of attrition from specialty training in secondary care - Gillian Vance; Bryan Burford; Megan E L Brown; Hannah Gillespie; Nicola Brennan (BMJ Open)
Background The healthcare workforce is in crisis. Despite a competitive selection process, a substantial number of doctors leave specialty training (ST) programmes prematurely. This attrition causes increased costs for the National Health Service, exacerbates workforce shortages and threatens quality and safety of care. It also increases pressure on trainees who remain, further compounding the risk of attrition. There is an urgent need to understand why doctors leave ST in order to find ways to maintain the training pipeline from ST to consultant.Objectives We aimed to understand what is known about why doctors choose to leave ST programmes in secondary care, to map current knowledge and identify avenues for future research.Eligibility criteria All studies which investigated why doctors leave ST programmes in secondary care were included.Sources of evidence Ovid Medline, Web of Science, SCOPUS and EMBASE were searched until January 2024. Descriptive codes were assigned to the findings of each study. These descriptive codes were reviewed and grouped together in broader categories.Charting methods Data was extracted and charted, and a qualitative content approach was used to synthesise data.Results A total of 6079 potentially relevant abstracts were retrieved, of which 23 were included in the final analysis. This included the experience of 1896 doctors who have left training and 454 programme directors. Doctors chose to leave training programmes because (1) they felt unsupported and underappreciated, (2) training was associated with unacceptable personal costs and (3) career prospects were unattractive.Conclusion There is a mismatch between trainees’ expectations of ST and the reality of being a trainee in ST. Understanding the issues which drive attrition and developing evidence-based solutions, has the potential to both reduce attrition, and improve the training experience for doctors in training more widely.